Synthesis of Mg1.5MnTi0.25O4 and Its Selectivity to Li+ Exchange - Wang, Lintong; Jiang, Jinhe (Asian Journal of Chemistry, 2013)
The ion-exchanger Mg1.5MnTi0.25O4 of inverse spinel type was prepared by means of the solid state reaction crystallization method. Its ion-exchange properties for alkali ions such as saturation capacity of exchange and distribution coefficient were determined. Mg1.5MnTi0.25O4 was characterized by X-ray diffraction method. The acid treatment of Mg1.5MnTi0.25O4 causes Mg+ extraction ratio to change from 30 to 78 %, while dissolution of Ti4+ is less than 8 %. This inorganic ion-exchanger (Mg1.5MnTi0.25O4) has the saturation capacity of exchange for Li+ higher than those for other alkali ions. The saturation capacity of exchange for Li+ reaches to 10.9 mmol/g, MgMnTi-900(H) has a higher selectivity of ion exchange for Li+ than for other alkali ions.